2020
DOI: 10.1093/cid/ciaa1073
|View full text |Cite|
|
Sign up to set email alerts
|

CYP2B6 Genotype and Weight Gain Differences Between Dolutegravir and Efavirenz

Abstract: Background Dolutegravir is associated with more weight gain than efavirenz. Loss-of-function polymorphisms in CYP2B6 result in higher efavirenz concentrations, which we hypothesized would impair weight gain among people living with human immunodeficiency virus (HIV; PLWH) starting efavirenz-based antiretroviral therapy (ART). Methods We studied ART-naive participants from the ADVANCE study randomized to the efavirenz /emtrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 21 publications
3
67
1
Order By: Relevance
“…Regarding NNRTIs, RPV has been associated with more weight gain than EFV [5]. In the ADVANCE study, data found that CYP2B6 was identified as a relevant factor: Slow EFV metabolizers on EFV had minimal weight gain, whereas rapid metabolizers gained as much weight as those on DTG, arguing that it was the lack of EFV toxicity that accounted for the difference, rather than a direct DTG effect [15]. Regarding the comparison between INSTIs and PIs, the recent pooled analysis of eight ART-na€ ıve randomized clinical trials [5] revealed a greater average weight gain at two years among patients treated with INSTIs, with 3.2 kg versus 1.9 kg among those treated with NNRTIs and 1.7 kg with PIs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding NNRTIs, RPV has been associated with more weight gain than EFV [5]. In the ADVANCE study, data found that CYP2B6 was identified as a relevant factor: Slow EFV metabolizers on EFV had minimal weight gain, whereas rapid metabolizers gained as much weight as those on DTG, arguing that it was the lack of EFV toxicity that accounted for the difference, rather than a direct DTG effect [15]. Regarding the comparison between INSTIs and PIs, the recent pooled analysis of eight ART-na€ ıve randomized clinical trials [5] revealed a greater average weight gain at two years among patients treated with INSTIs, with 3.2 kg versus 1.9 kg among those treated with NNRTIs and 1.7 kg with PIs.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated percentage change in weight from baseline to week 48. Body composition measures using DXA (Discovery DXA System, software version APEX 4.6.0.1, Hologic, Bedford, MA, USA) at baseline and week 48 were used to estimate changes in abdominal visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) 12,15 . The percentage change in mass from baseline to week 48 was calculated for VAT and SAT.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple investigators have assessed the effects of individual genetic variations on weight change with EFV in treatment initiation and switch studies. For example, researchers compared weight change after treatment initiation with EFV or DTG based on CYP2B6 genetic loss-of-function polymorphism, which leads to higher EFV concentrations [ 65 ]. Based on 342 participants receiving DTG and 168 receiving EFV, the CYP2B6 EFV metabolizer genotype significantly influenced likelihood of weight gain while taking EFV; extensive metabolizers gained similar amounts of weight to the group taking DTG.…”
Section: Integrase Strand Transfer Inhibitorsmentioning
confidence: 99%